FILOLOG STUDENTLERDIŃ LINGVOMETODIKALÍQ KOMPETENCIYASÍ HÁM MASHQALALARDÍŃ TALQÍLANÍWÍ - Bekimbetova, G. (ILIM hám JÁMIYET, 2024)
This article analyzes the linguistic and methodological competencies of university philology students. The article analyzes the problems aimed at the development of linguistic and methodological competence of students of philology. Suggestions and recommendations on the topic are given.